2012
DOI: 10.4085/1062-6050-47.5.02
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Outbreaks in Competitive Sports, 2005–2010

Abstract: Context Old, evolving, and new infectious agents continually threaten the participation of competitors in sports. Objective To provide an update of the medical literature on infectious disease outbreaks in sport for the last 5 years (May 2005–November 2010). Main Outcome Measure(s) A total of 21 outbreaks or clusters were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Types of skin infections in our study were also similar to those identified previously, 1,3,10 with herpes simplex I (41.1%) and impetigo (10.7%) identified as common pathogens. Tinea versicolor was the most frequent fungal infection identified, which contrasts with previous NCAArelated research 3 in which ringworm occurred most often among wrestlers.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Types of skin infections in our study were also similar to those identified previously, 1,3,10 with herpes simplex I (41.1%) and impetigo (10.7%) identified as common pathogens. Tinea versicolor was the most frequent fungal infection identified, which contrasts with previous NCAArelated research 3 in which ringworm occurred most often among wrestlers.…”
Section: Discussionsupporting
confidence: 88%
“…Previous literature on collegiate wrestlers' skin infections has been limited to case studies 9,[16][17][18][19] or broader descriptive studies in which skin infections represented 1 combined injury category. 1,3,7,10,14 Therefore, these data provide the largest in-depth examination of recent skin infection data from multiple collegiate wrestling teams, which can help inform skin infectionprevention protocols. According to the National Athletic Trainers' Association position statement 23 on skin diseases, infection-control policies are recommended for all collegiate institutions, including cleaning and disinfecting of all facilities, encouraging hand hygiene, and ensuring the practice of athlete hygiene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…locker rooms, sport meetings) with a great number of persons and in particular for indoor sports (wrestling, gymnastics, etc. ), close contact between athletes is common, with increased risk of airborne infection [20]. During international competitions, athletes are hosted in villages where they share the same services and in these settings there is a high risk of outbreak onset (e.g.…”
mentioning
confidence: 99%